Pengaruh Biaya Iklan dan Promosi Terhadap Penjualan PT Industri Jamu dan Farmasi Sido Muncul Tbk Periode 2019-2023 - Wilandari, Angestika; Naufalia, Viani; Windasari, Vicky; Shadiq Helmy, Moehammad (Jurusan Akuntansi Politeknik Negeri Padang, 2024)
This research was conducted to get the result of relationship analysis of advertising and promotion cost toward sales of PT Industri Jamu dan Farmasi Sido Muncul Tbk. The type of data used is secondary data sourced from the financial statements of PT Industri Jamu dan Farmasi Sido Muncul Tbk. The period of research conducted is for five years, namely 2019-2023 by considering the background of the Covid-19 pandemic. PT Industri Jamu dan Farmasi Sido Muncul Tbk was considered as one of the companies that implemented cost efficiency optimally during the duration before and after Covid-19. The fluctuation of promotion and advertising cost toward sales performance was experienced by PT Industri Jamu dan Farmasi Sido Muncul Tbk with the highest promotion and advertising cost condition in 2022 but the highest sales in 2021. zvertising and promotion costs, while the rest is influenced by variables that are not explained in this study. The resulting relationship is positive, meaning that if there is an increase in advertising and promotion costs, PT's sales performance will increase. Sido Muncul Herbal Medicine and Pharmaceutical Industry Tbk.